The methodology of al-Zamakhsharī in his exegesis al-Kashshāf - Mennad, Brahim; Dahmani, Hamza (The International tax journal, 2026)
This study seeks to present the exegetical methodology adopted by al-Zamakhsharī in his commentary al-Kashshāf, examining how he presents his material and the criteria he employs to attain the ultimate objective of discerning comprehensive or partial meanings and significations. It further considers his scholarly apparatus in interpreting the Noble Qurʾān, first from the perspective that he was among the most accomplished and deeply verses scholars in the intricacies and secrets of the Arabic language, and second, in view of his position as one of the leading figures of the Muʿtazilite school, which accords primacy to reason and establishes it as a fundamental principle above all else. The study also explores the extent to which this intellectual orientation influences al-Zamakhsharī's views and exegetical interpretations.